Consumption and Fractional Differencing: Old and New Anomalies - Haubrich, Joseph G. (The Review of Economics and Statistics, 1993)
A calculation of the stochastic properties of consumption when income follows a fractional stochastic process, showing how this may explain excess-smoothness results noted in previous studies.